2006
DOI: 10.1007/s00405-006-0157-0
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prognostic significance of qualitative olfactory dysfunction

Abstract: We investigated the frequency and prognostic significance of qualitative olfactory dysfunction (parosmia, phantosmia) in a retrospective patient based study. A total of 392 patients with impairment of olfaction were tested at least two times for their olfactory function using the "Sniffin' Sticks". The mean interval between the first and the last test was 11 months. At the first visit 34% of all patients reported parosmia. Parosmia was most frequent in patients with postinfectious olfactory loss (56%), and les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
130
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 19 publications
4
130
2
8
Order By: Relevance
“…Unfortunately, these authors did neither differentiate between parosmia and phantosmia nor did they specify after what time lapse recovery occurred. Reden et al [1] reported parosmia to disappear or weaken in 29% and phantosmia in 53% of followed-up patients after an observational period of almost 1 year. This is similar to our rate after a mean observation of 6 years, which suggests that most phantom smells disappear within the first year, and very little supplementary recovery can be expected after this period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, these authors did neither differentiate between parosmia and phantosmia nor did they specify after what time lapse recovery occurred. Reden et al [1] reported parosmia to disappear or weaken in 29% and phantosmia in 53% of followed-up patients after an observational period of almost 1 year. This is similar to our rate after a mean observation of 6 years, which suggests that most phantom smells disappear within the first year, and very little supplementary recovery can be expected after this period.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the pioneering work of Leopold and colleagues [2,13,14] who attempted to systematically describe, diagnose and treat phantosmia, little clinically useful knowledge is available to the otorhinolaryngologist. Recently, Reden et al [1] identified phantosmia to potentially occur in almost all conditions affecting the sense of smell. Amongst investigated cases, idiopathic phantosmia was the most frequent diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these symptoms seem less frequent when related to sinonasal disease than to other etiologies (i.e. post-infectious, post traumatic) and Reden et al (2007) reported incidence of parosmia and phantosmia in patients with CRS of 28% and 7%, respectively.…”
mentioning
confidence: 95%